Composite solid electrolyte material for solid positive electrode and preparation method and application thereof
A composite solid electrolyte with evenly distributed carbon in sulfide electrolytes addresses decomposition issues, enhancing conductivity and stability in lithium-ion batteries by forming a homogeneous body, thus improving battery performance and reducing production costs.
Patent Information
- Application Number
- CN202211117552.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-09-14
AI Technical Summary
Existing sulfide-based solid electrolytes for lithium-ion batteries face issues with decomposition due to added carbon-containing conductive agents, affecting ion conductivity and requiring improvements in both electronic and ion conductivity to enhance battery performance and safety.
A composite solid electrolyte material with evenly distributed carbon elements within the sulfide electrolyte, forming a homogeneous body to suppress decomposition and improve both internal and inter-particle conductivity, achieving a short-range lithium ion-long-range electron mixed conductor.
The composite electrolyte material enhances electronic and ionic conductivity, ensuring stable battery performance without additional carbon agents, improving cycle stability and reducing production costs through a simple and efficient preparation method.
Smart Images

Figure CN115588741B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a composite solid electrolyte material for a solid positive electrode and a preparation method and application thereof. Background Art
[0002] Since its commercialization in the early 1990s, lithium-ion secondary batteries have developed rapidly due to their advantages such as high energy density and long service life. However, the lithium-ion batteries commonly used at present are liquid-phase batteries, which contain flammable organic electrolytes and therefore pose serious safety hazards. In recent years, the frequent occurrence of safety accidents in liquid-phase lithium-ion power batteries has greatly restricted the further use of this system. The use of non-flammable inorganic solid materials as lithium-ion battery electrolytes can not only eliminate the safety hazards caused by organic electrolyte leakage and thermal runaway inside the battery during battery use, but also can be used under extreme conditions such as high and low temperatures, further enhancing the value of lithium secondary batteries and expanding their application areas. Therefore, the research and development of high-performance solid electrolyte materials is a key content to promote the commercialization of solid-state batteries.
[0003] Among solid electrolytes, sulfide-based solid electrolytes have attracted much attention as solid electrolytes with very high lithium ion conductivity. Since solid electrolytes have the characteristics of high ion conductivity and low electron conductivity, when solid electrolyte materials are used in solid positive electrodes, additional carbon-containing conductive agents such as graphite need to be added to establish electron transmission channels. Non-patent literature shows (Adv. Energy Mater. 2016, 6, 1501590) that additionally added carbon materials will cause sulfide solid electrolyte materials to decompose, which will also affect the ion conductivity of the electrolyte material, and currently carbon-containing conductive agents are commonly used in lithium batteries. Therefore, it is necessary to provide a stable lithium ion-electron mixed conductor solid electrolyte material to reduce or avoid the use of carbon-containing conductive agents in solid positive electrodes.
[0004] Chinese patent CN111194494A reports a method for improving the electronic conductivity of oxide solid electrolytes by doping. However, the inventors found in actual work that this method is not suitable for improving the electronic conductivity of sulfide solid electrolytes. Doping can only adjust the electronic conductivity of sulfide solid electrolyte materials within an order of magnitude, but cannot achieve an order of magnitude improvement. The slight change in electronic conductivity cannot achieve the purpose of realizing lithium ion-electron mixed conductor solid electrolyte materials.
[0005] Chinese patent CN112768762A reports a mixture of sulfide solid electrolyte and organic matter for sintering. The problems with this method are: 1) the solid electrolyte and organic matter mixture before sintering is not a solid electrolyte; 2) the sintering of the sulfide solid electrolyte needs to be carried out in an inert atmosphere such as nitrogen and argon, and the organic matter selected in the patent cannot be decomposed into carbon in an inert atmosphere, so no carbon-containing solid electrolyte can be obtained after heat treatment; 3) the patent does not specify the atmosphere during the heat treatment process. If the heat treatment is carried out in an atmosphere containing oxygen, the ion conductivity of the sulfide solid electrolyte will be seriously reduced, which is difficult to meet the use requirements of all-solid-state batteries; 4) the patent does not require the ion conductivity and electron conductivity of the electrolyte material. The inventor found during the research process that suitable ion conductivity and electron conductivity are particularly important for the performance of the material in the solid-state battery.
[0006] Chinese patent CN111403806A reports a carbon-coated solid electrolyte material, its preparation method and use. This material consists of a solid electrolyte core and a carbon layer shell. Its essence is still a composite of electrolyte and carbon material, and it cannot solve the problem of decomposition of sulfide solid electrolyte caused by carbon material; and this method only solves the conductivity problem between electrolyte particles, but cannot solve the conductivity problem inside the particles.
[0007] In view of this, it is necessary to provide a sulfide solid electrolyte material for solid positive electrode, which is a short-range lithium ion-long-range electron mixed conductor, and can provide lithium ion and electron channels in the positive electrode layer without adding additional conductive agents. The improvement of the electronic conductivity of the electrolyte material effectively avoids the decomposition of the sulfide solid electrolyte caused by the addition of conductive agents. The material should solve the problem of electronic conductivity inside and between electrolyte particles at the same time. At the same time, a simple and efficient preparation method should also be provided, which must be able to be industrially scaled up and cost-controlled. Summary of the invention
[0008] In view of the deficiencies of the prior art, the object of the present invention is to provide a composite solid electrolyte material for a solid positive electrode and a preparation method thereof, as well as the application of the obtained material in a solid-state lithium secondary battery.
[0009] Specifically, the present invention first provides a composite solid electrolyte material for a solid positive electrode, wherein the composite solid electrolyte material comprises a sulfide electrolyte, wherein the sulfide electrolyte comprises lithium ions and anions containing at least sulfur element;
[0010] The composite solid electrolyte material also contains carbon element, and the carbon element is evenly distributed in the sulfide electrolyte;
[0011] Based on the mass of the sulfide electrolyte, the mass fraction of the carbon element is 150 ppm to 10%.
[0012] The present invention has found that by evenly distributing the carbon material inside the sulfide solid electrolyte material to form a homogeneous body, the interface between the added conductive carbon and the carbon-free solid electrolyte is eliminated, that is, the ion conductivity / electronic conductivity gradient at the interface is eliminated, and thus the decomposition of the sulfide electrolyte caused by this can be effectively suppressed. The evenly distributed carbon element also improves the electronic conductivity inside and between the solid electrolyte particles, and a short-range lithium ion-long-range electron mixed conductor can be obtained. Thus, lithium ions (ionic conductivity ≥1.0×10 -4 S / cm, preferably ≥1.0×10 -3 S / cm) and electron channels (electronic conductivity ≥1.0×10 -6 S / cm, preferably ≥1.0×10 -5 S / cm), effectively avoiding the decomposition of the sulfide solid electrolyte caused by the addition of conductive agents, and showing better cycle stability compared with the method of adding conductive carbon or coating carbon materials on the surface of electrolyte particles. In addition, the preparation method of the sulfide solid electrolyte material for the solid positive electrode is simple and effective, combined with the preparation process of the electrolyte material, and the production cost is low.
[0013] Preferably, the mass fraction of the carbon element is 500ppm to 1% based on the mass of the sulfide electrolyte. The present invention finds that when the carbon content exceeds 1%, the ionic conductivity will decrease significantly, and the significant decrease in ionic conductivity will lead to a serious decrease in the performance of the solid-state battery.
[0014] Preferably, the ratio of the ionic conductivity to the electronic conductivity of the sulfide solid electrolyte is not greater than 3000.
[0015] The present invention also provides a method for preparing the composite solid electrolyte material for the solid positive electrode, which is simple and effective, combined with the preparation process of the electrolyte material, and has low production cost. Specifically, it includes the following steps:
[0016] 1) Weigh various raw materials according to the stoichiometric ratio of the sulfide electrolyte, and weigh the carbon-containing additive A according to the stoichiometric ratio of the carbon element;
[0017] 2) mixing the various raw materials and the carbon-containing additive A in step 1) uniformly to obtain a mixed intermediate;
[0018] 3) The mixed intermediate in step 2) is subjected to heat treatment in an inert atmosphere.
[0019] Preferably, the chemical formula of the carbon-containing additive A in step 1) is C i H 2j O j, wherein i≥4, j≥0. The present invention finds that, compared with other organic substances, the ionic conductivity and electronic conductivity of the composite solid electrolyte material for solid positive electrode obtained by using organic substances meeting the requirements of the above formula as carbon-containing additives are more excellent.
[0020] In a preferred embodiment, the chemical formula of the carbon-containing additive A is C4H8O4, C5H 10 O5、C6H 12 O6, C 12 H 22 O 11 , C 42 H 72 O 36 One or more of the following.
[0021] Preferably, the mixing method in step 2) is wet mixing or dry mixing.
[0022] Preferably, the mixing in step 2) is performed by ball milling, with a rotation speed of 200 to 500 rpm and a time of 5 to 24 hours.
[0023] Preferably, the inert atmosphere in step 3) is nitrogen, argon or a nitrogen / argon mixture.
[0024] The method for preparing the sulfide electrolyte raw material of the present invention is arbitrary, and the sulfide electrolyte raw material may be purchased or manufactured. Here, an example of a method for manufacturing a composite solid electrolyte material for a solid positive electrode is described.
[0025] For example, Li2S, LiCl, P2S5, and carbon-containing additives can be weighed in proportion, mixed, heat-treated in an inert atmosphere, and crushed to obtain the product.
[0026] The present invention also provides a positive electrode layer for a solid-state battery, which is prepared from the composite solid electrolyte material for a solid positive electrode, or the composite solid electrolyte material for a solid positive electrode prepared by the above method, and a positive electrode material.
[0027] The present invention also provides an all-solid-state lithium secondary battery, comprising a positive electrode layer, a negative electrode layer and a solid electrolyte layer, wherein the positive electrode layer is the positive electrode layer for the solid-state battery described above. The electrolyte layer can be any solid electrolyte material.
[0028] The beneficial effects of the present invention are:
[0029] The composite solid electrolyte material for the solid positive electrode provided by the present invention is a lithium ion-electron mixed conductor, which can greatly reduce or avoid the use of carbon-containing conductive agents in the solid positive electrode, and effectively avoid the decomposition of the sulfide solid electrolyte and the attenuation of the cycle performance caused by the addition of conductive agents.
[0030] At the same time, the present invention also provides a simple and efficient preparation method with simple steps and low production cost; at the same time, the obtained sulfide solid electrolyte material for solid positive electrode has controllable ion conductivity and has excellent performance when used as an electrolyte material in the positive electrode of an all-solid-state lithium battery.
[0031] Therefore, the sulfide solid electrolyte material for positive electrode and the preparation method thereof provided by the present invention are expected to solve the problem of large-scale use of sulfide solid electrolyte materials in oxide positive electrodes. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The electron conductivity test spectra of the carbon-containing sulfide electrolyte obtained in Example 1 and the carbon-free sulfide electrolyte obtained in Comparative Example 1 are shown. DETAILED DESCRIPTION
[0033] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention are within the scope of the present invention.
[0034] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. All reagents or instruments without manufacturer specified are conventional products that can be purchased through regular channels.
[0035] Solid electrolyte preparation
[0036] Examples 1 to 10, Comparative Examples 1 to 8
[0037] In the glove box, various raw materials (Li2S, LiCl, LiI, P2S5, SiS2, GeS2) were weighed according to the proportion of the chemical formula of the electrolyte materials in Table 1, and the total weight of various raw materials remained unchanged at 5g, and placed in a 50ml zirconia ball mill; the carbon-containing additive C6H 12 O6, add into the ball mill; finally add 50g of zirconia balls with a diameter of 5mm.
[0038] Place the sealed ball mill jar on the ball mill, set the speed to 400 rpm, and ball mill for 12 hours. Collect the ball-milled samples and seal them in a vacuum quartz tube for calcination at a specific temperature of 350 to 650°C. The calcination temperature is controlled by program temperature rise, and the temperature naturally drops to 50°C after sintering to obtain the positive electrode solid electrolyte.
[0039] Comparative Example 9
[0040] In a glove box, various raw materials were weighed according to the proportion of the chemical formula of the electrolyte material of Comparative Example 9 in Table 1, with the total weight of various raw materials kept unchanged at 5g, and placed in a 50ml zirconia ball mill; the carbon-containing additive C6H8O7 was weighed according to the proportion of carbon content in Table 1 and added to the ball mill; finally, 50g of zirconia balls with a diameter of 5mm were added.
[0041] Place the sealed ball mill jar on the ball mill, set the speed to 400 rpm, and ball mill for 12 hours. Collect the ball-milled samples and seal them in a vacuum quartz tube for calcination. The calcination temperature is controlled by program temperature rise. After sintering, the temperature naturally drops to 50°C to obtain the positive electrode solid electrolyte.
[0042] Comparative Example 10
[0043] In a glove box, various raw materials were weighed according to the proportions of the chemical formula of the electrolyte material of Comparative Example 10 in Table 1, with the total weight of the raw materials kept constant at 5 g. The raw materials were placed in a 50 ml zirconia ball mill, and finally 50 g of zirconia balls with a diameter of 5 mm were added.
[0044] Place the sealed ball mill jar on the ball mill, set the speed to 400 rpm, and ball mill for 12 hours. Collect the ball-milled samples and seal them in a vacuum quartz tube for calcination. The calcination temperature is controlled by program temperature rise. After sintering, the temperature naturally drops to 50°C to obtain a carbon-free solid electrolyte.
[0045] In the above carbon-free solid electrolyte, the carbon-containing additive C6H 12 O6, add to the ball mill, keep the total weight of various raw materials at 5g, place in a 50ml zirconia ball mill, and finally add 50g of zirconia balls with a diameter of 5mm.
[0046] Place the sealed ball mill jar on the ball mill, set the speed to 400 rpm, and ball mill for 12 hours. Collect the ball-milled samples and seal them in a vacuum quartz tube for calcination. The calcination temperature is controlled by program temperature rise. After sintering, the temperature naturally drops to 50°C to obtain a carbon-coated positive electrode solid electrolyte material.
[0047] Solid electrolyte material ion conductivity test
[0048] Test the ion conductivity of the solid electrolyte material for the positive electrode obtained in Comparative Examples 1 to 10 and Examples 1 to 10. In a glove box, weigh 150 mg of the solid electrolyte material and put it into a mold (10 mm in diameter), apply a pressure of 300 MPa to it, and keep it for 60 seconds to form. Add an appropriate amount of carbon nanotubes on both sides of the pressed electrolyte sheet, apply a pressure of 300 MPa to it, and keep it for 30 seconds to form. Finally, put the mold into the shell and tighten the screws. Let the assembled mold stand at room temperature, and perform the ion conductivity test after the temperature stabilizes. The results are shown in Table 1.
[0049] Solid electrolyte material electronic conductivity test
[0050] The ion conductivity of the solid electrolyte material for the positive electrode obtained in Comparative Examples 1 to 10 and Examples 1 to 10 was tested. In a glove box, 150 mg of the solid electrolyte material was weighed and placed in a mold (10 mm in diameter), and a pressure of 300 MPa was applied to it, and the molding was maintained for 60 seconds. Finally, the mold was placed in the housing and the screws were tightened. The assembled mold was left to stand at room temperature, and the ion conductivity test was performed after the temperature stabilized. The results are shown in Table 1.
[0051] Figure 1 The electron conductivity test spectra of the carbon-containing sulfide electrolyte obtained in Example 1 and the non-carbon sulfide electrolyte obtained in Comparative Example 1 are shown in FIG. As can be seen from the figure, the equilibrium current of the carbon-containing sulfide electrolyte obtained in Example 1 is much higher than the equilibrium current of the non-carbon sulfide electrolyte obtained in Comparative Example 1, indicating that the electrolyte has a higher electron conductivity. After calculation, the electron conductivity in Example 1 is 3.2×10 -6 S / cm, while the electron conductivity in Comparative Example 1 is 1.9×10 -9 S / cm.
[0052] Simulating battery assembly
[0053] The positive electrode solid electrolyte materials obtained in Examples 1 to 10 and Comparative Examples 1 to 10 were prepared according to the positive electrode material (LiNi 0.6 Co 0.2 Mn 0.2 O2, NCM622): electrolyte material = 70:30 (mass ratio) Weigh two materials, weigh acetylene carbon according to the amount of conductive agent added in Table 1, and grind the above three materials in a mortar in a glove box for 20 minutes to mix them evenly. The above mixture is used as the positive electrode powder, the metal Li sheet is used as the negative electrode, and Li6PS5Cl is used as the electrolyte layer to assemble an all-solid-state secondary battery.
[0054] The data of the first-week discharge capacity and the discharge capacity after 100 cycles of the simulated batteries prepared using the positive electrode solid electrolyte materials of Examples 1 to 10 and Comparative Examples 1 to 10 are shown in Table 1.
[0055] Table 1 Ionic conductivity, electronic conductivity and electrical performance data of Examples 1 to 10 and Comparative Examples 1 to 10
[0056]
[0057]
[0058] As can be seen from Table 1, the composite solid electrolyte material for the solid positive electrode provided by the present invention has high electronic conductivity, can simultaneously play the dual role of ion conduction and electron conduction, and can ensure the normal performance of the capacity of NCM622 with little or no use of an additional carbon-containing conductive agent. The reduction or elimination of the carbon-containing conductive agent can greatly improve the stability of the sulfide solid electrolyte in the solid positive electrode, thereby greatly improving the cycle stability of the battery.
[0059] The above embodiments are merely descriptions of preferred implementation modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary engineers and technicians in the field should all fall within the protection scope of the claims of the present invention.
Claims
1. A composite solid electrolyte material for a solid positive electrode, characterized in that: The composite solid electrolyte material comprises a sulfide electrolyte, wherein the sulfide electrolyte comprises lithium ions and anions containing at least sulfur element; The composite solid electrolyte material also contains carbon element, and the carbon element is evenly distributed in the sulfide electrolyte; The mass fraction of the carbon element is 150ppm to 10% based on the mass of the sulfide electrolyte; The method for preparing the composite solid electrolyte material for the solid positive electrode is characterized by comprising the following steps: 1) Weigh various raw materials according to the stoichiometric ratio of the sulfide electrolyte, and weigh the carbon-containing additive A according to the stoichiometric ratio of the carbon element; the chemical formula of the carbon-containing additive A is C i H 2j O j , where i≥4, j>0; 2) uniformly mixing the various raw materials and the carbon-containing additive A in step 1) to obtain a mixed intermediate; 3) The mixed intermediate in step 2) is heat treated in an inert atmosphere.
2. The composite solid electrolyte material for solid positive electrode according to claim 1, characterized in that: Based on the mass of the sulfide electrolyte, the mass fraction of the carbon element is 500ppm~1%.
3. The composite solid electrolyte material for solid positive electrode according to claim 1 or 2, characterized in that: The ratio of the ionic conductivity to the electronic conductivity of the sulfide electrolyte is not greater than 3000.
4. The composite solid electrolyte material for solid positive electrode according to claim 1, characterized in that: The chemical formula of the carbon-containing additive A is C4H8O4, C5H 10 O5、C6H 12 O6, C 12 H 22 O 11 , C 42 H 72 O 36 One or more of the following.
5. The composite solid electrolyte material for solid positive electrode according to claim 1 or 4, characterized in that: The mixing in step 2) is ball milling with a rotation speed of 200-500 rpm and a time of 5-24 h.
6. The composite solid electrolyte material for solid positive electrode according to claim 1 or 4, characterized in that: The inert atmosphere in step 3) is nitrogen, argon or a nitrogen / argon mixture.
7. A positive electrode layer for a solid-state battery, characterized in that: A composite solid electrolyte material for a solid positive electrode as described in any one of claims 1 to 6.
8. An all-solid-state lithium secondary battery, comprising a positive electrode layer, a negative electrode layer and a solid electrolyte layer, characterized in that: The positive electrode layer is the positive electrode layer for a solid-state battery according to claim 7.
Citation Information
Patent Citations
Mixed ionic and electronic conductor for solid state battery
CN111194494A
Carbon-coated solid electrolyte material as well as preparation method and application thereof
CN111403806A
Carbon-containing sulfide solid electrolyte for solid-state lithium battery and preparation method of carbon-containing sulfide solid electrolyte
CN112768762A
Preparation method of lithium ion battery solid electrolyte material Li7La3Zr2O12
CN103594725A
Sulfide solid electrolyte with stable performance and preparation method and application thereof
CN111883822A
